Level of awareness about diabetes among adults attending services at Entebbe Grade B Hospital, Wakiso District.A Cross-sectional study. - Kasaaliita, Paul; Okwany , Jimmy; Nansereko, Hasifah; Ssemuwemba, Franscisco; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student’s Journal of Health Research Africa, 2026)
Background: Awareness about diabetes is an important component in the prevention, early detection, and effective management of the disease. Therefore, this study aims to assess the level of awareness about diabetes among adults attending services at Entebbe Grade B Hospital in Wakiso District. Methodology: Quantitative data were collected using structured questionnaires with closed-ended questions from adults attending services at Entebbe Grade B Hospital in Wakiso District. The completed questionnaires were checked for completeness, coded, and entered into Microsoft Excel for analysis. Data were analyzed using descriptive statistics such as frequencies and percentages. Results: All 35 (100%) participants had heard about diabetes. Common complications of poorly managed diabetes included poor vision/sight 7 (20%), delay in wound healing 5 (14%), and severe headache 23 (66%), with no participants having experienced none. 33 (94%) of the participants believed that stress and poor sleep could affect their blood sugar levels, whereas only 2 (6%) did not believe it. Conclusion: Adults attending services at Entebbe Grade B Hospital in Wakiso District were generally aware of diabetes since all participants had heard about the disease. Recommendation: Healthcare workers at Entebbe Grade B Hospital should strengthen patient health education on diabetes causes, risk factors, complications, and management. Regular awareness programs should be conducted to improve patients’ understanding of the disease.